Association between Multiple Myeloma and Ulcerative Colitis: A Cross-Sectional Analysis - Ayrton Bangolo; Sowmya Sagireddy; Paul Desrochers; Imane Laabidi; Vignesh K. Nagesh; Amer Jarri; Imranjot Sekhon; Youssef Laabidi; Deeksha Muralidhar; Adarshpreet Singh; Paranjyothy R. P. Sanjeeva; Damanpartap S. Sandhu; et al. (Diseases, 2023)
Background and Aims: Multiple myeloma (MM) is a plasma cell dyscrasia that is common among patients with autoimmune diseases. However, the association between ulcerative colitis (UC) and multiple myeloma (MM) is yet to be established. We aimed to evaluate the prevalence of MM among patients with UC in the United States. Methods: This cross-sectional cohort analysis used the National Inpatient Sample from 2015–2018 to assess the overall MM prevalence among patients with and without UC, and within specific demographic subgroups. Prevalences were compared using a logistic regression model controlling for sex and age. Results: The crude prevalence of MM among patients with UC (n = 1750) compared with patients without UC (n = 366,265) was 0.44% vs. 0.37%, respectively. Patients with UC had increased overall odds of having MM (odds ratio (OR), 1.26). Males with UC had higher prevalence of MM (53.7% vs. 46.3%, respectively) than females. Patients with UC and MM were more likely to be African American than White (15.6% vs. 9.2%, respectively). Patients with UC age >64 had a higher prevalence of MM than those aged below 65 (70.9% vs. 29.1%, respectively). Patients with UC who were obese (BMI > 30) had a higher prevalence of MM than those who were non-obese (12.6% vs. 8.3%). Conclusions: Overall, UC appears to be associated with MM. This association can be particularly observed in specific demographic groups, such as obese, African American males, or patients >64 years of age. Thus, a high degree of clinical suspicion for MM is warranted, even with minimal symptomatology, in patients with UC, in particular among elder, obese, and African American males.